(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Zasadniczym aktem prawnym, który przewiduje możliwość tworzenia samorządów zawodowych, jest Konstytucja Rzeczypospolitej Polskiej. Zgodnie z art. 17 ust. 1 ww. aktu, w drodze ustawy można tworzyć samorządy zawodowe, reprezentujące osoby wykonujące zawody zaufania publicznego i sprawujące pieczę nad należytym wykonywaniem tych zawodów w granicach interesu publicznego i dla jego ochrony oraz inne rodzaje samorządu, które nie mogą naruszać wolności wykonywania zawodu ani ograniczać wolności podejmowania działalności gospodarczej. Przepis umieszczono w rozdziale pierwszym ustawy zasadniczej, gdzie zawarte zostały zasady najbardziej fundamentalne, składające się łącznie na ogólną charakterystykę Rzeczypospolitej. Oznacza to, że bez którejkolwiek z zasad tam zawartych, państwo polskie posiadałoby odmienny charakter. Self-governments of professions of public trust are empowered in the Constitution, where it derives its rank. Empowerment of activities of Professional self-government is therefore a very strong and unique. Article 17 of the Constitution establishes two types of self-governments. The legal situation of both types of local government referred in Art. 17 of the Constitution is not identical. Art. 17 Par. 1 of the Constitution shows the basic objectives of the functioning of professional self-governments and „the other types of self-government”, which states in Art.17 Par. 2, does not ascribe objectives, while establishes the limits of their influence. These self-governments cannot in any way infringe the freedom to practice the profession or limit the freedom to undertake economic activity. These reservations do not extend, however, to professional self-governments representing the professions of public trust, which may, in some cases even be limited to a certain extent the freedom of the profession or business for the purposes for which they have been implementing. The essence of the professional self-government mentioned in Art. 17 par. 1 of the Constitution is the exercise by a separate entity, in the limits set by law, a public authority. This is possible by giving him a personality of public law and equipping it with powers to exercise part of the public authority, which can perform without management and another entity interference, such as the state. However, staying under control in this independent action with the authorization of their authority. That relative independence from the state union of professional self- governments and their powers mean that they act as an intermediary between the state and the people performing specific professions, limited direct impact of the administration on certain professional groups.